Racial Identity and Voting: Conceptualizing White Identity in Spatial Terms. Issue 2 (16th May 2018) - Weller, Nicholas; Junn, Jane
Abstract : Recent political events have prompted an examination of the analytical tools and conceptual frameworks used in political science to understand voting and candidate choice. Scholars in the behavioral tradition have highlighted the empirical relationship between racial resentment and anti-black affect among white voters during and after President Obama's successful run for re-election. The theoretical role of white identity within the context of the privileged status of this racial group has seen much less scholarly attention by political scientists, particularly with respect to racial group identification and its implications. To address this lacuna, we argue that racial identification among white voters can be conceived of as a utility-based trait relevant to candidate choice, combining a social-psychological approach of group membership together with a rational choice perspective. This conceptualization of the political utility of white racial identity provides wider conceptual latitude for empirical tests and explanations of voting in U.S. elections.